Barriers and facilitators to delivering bystander cardiopulmonary resuscitation in deprived communities: a systematic review. (January 2023) - Uny, I; Angus, K; Duncan, E; Dobbie, F
Background: There is a higher incidence of cardiac arrest in economically deprived areas; however, data show that bystander cardiopulmonary resuscitation (CPR) in those areas is lower. This results in lower survival rates, placing those communities at a double disadvantage. This systematic review explored the barriers and facilitators to engaging with bystander CPR in deprived communities. Methods: Studies were eligible for inclusion if they addressed any barrier or facilitator to performing bystander CPR or being trained in CPR or training others. Studies had to either be set in a deprived area or examine a deprived population. Selected studies were published between January 2000 and December 2017 and reported on primary research. No language limitations were applied. Searches were conducted in the following databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, PsycINFO, PubMed, and Web of Science Core Collection. Unpublished 'grey' literature was also searched as well as the reference lists of any relevant studies. Results: The systematic review highlighted several main factors acting as barriers or facilitators to engaging with bystander CPR in deprived communities: (1) the willingness to learn or perform CPR, (2) the confidence to perform CPR, and (3) self-reported likelihood of performing CPR. The review also revealed additional barriers to engaging with CPR which are specific to – or more acute for – individuals from socioeconomically deprived backgrounds or areas. Discussion: We found little evidence suggesting that the willingness to perform or learn bystander CPR is lower in deprived communities compared to the general population. However, the confidence to perform CPR in deprived communities was affected by some measures of socioeconomic status. The results also crucially highlighted other barriers more acute in deprived communities: the risk to personal safety in administering CPR; the fear of legal consequences; and the lack of community cohesion and other cultural barriers.